Intron 5 alpha of the COXI gene of yeast mitochondrial DNA is a mobile group I intron. - Moran, J V (1992)
We have found that intron 5 alpha of the COXI gene (al5 alpha) of yeast mtDNA is a mobile group I intron in crosses between strains having or lacking the intron. We have demonstrated the following hallmarks of that process: 1) co-conversion of flanking optional intron markers; 2) mutations that truncate the intron open reading frame block intron mobility; and 3) the intron open reading frame encodes an endonuclease activity that is required for intron movement. The endonuclease activity, termed I-Sce IV, cleaves the COXI allele lacking al5 alpha near the site of intron insertion, making a four-base staggered cut with 3' OH overhangs. Three cloned DNAs derived from different forms of the COXI gene, which differ in primary sequence at up to seven nucleotides around the cleavage site, are all good substrates for in vitro I-Sce IV cleavage activity. Two of the strains from which these substrates were derived were tested in crosses and are comparably efficient as al5 alpha recipients. When compared with omega mobility occurring simultaneously in one cross, al5 alpha is less efficient as a mobile element.